REAKTIFASI INDONESIA AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT(IA CEPA) TAHUN 2016 - Rionaldo, Dedy; Damayanti, Christy; Haqqi, Halifa (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
This study describes and analyzes the Reactivation of the Indonesia Australia Comprehensive Economic Partnership Agreement (IA CEPA) in 2016. In improving bilateral relations, Indonesia and Australia have agreed to implement strategic economic cooperation negotiations known as the Indonesia Australia Comprehensive Economic Partnership Agreement (IA CEPA). In the development of cooperation negotiations, it was halted in 2013 due to conditions of fluctuating political relations. Nonetheless, in the end Indonesia and Australia agreed to carry out a reactivation in 2016. The researchers used the theory of bilateral relations and bilateral economic cooperation. This study aims to analyze how the reactivation of the Indonesia Australia Comprehensive Economic Partnership Agreement in 2016. The research method used in this study is a qualitative research method with secondary data collection sources. The study was conducted through the collection of documents with descriptive explanation. From research data on the Reactivation of IA-CEPA in 2016, researchers found that although in bilateral relations often experienced fluctuating relationships, basically the two countries have an interest through cooperative relations. Because with the agreement on the re-activation of IA-CEPA cooperation negotiations, it will improve prosperity through economic cooperation so that the economic interests can be achieved through comprehensive cooperative relations. Keywords:Reactivatioan, Indonesia Australia Comprehensive Economic Partnership Agreement, Bilateral Economic Cooperation